PISA SYNDROME IN PARKINSON'S DISEASE–A MOBILE OR FIXED DEFORMITY?. Issue 11 (9th October 2013) - Doherty, Karen; Davagnanam, Indran; Molloy, Sean; Silveira–Moriyama, Laura; Lees, Andrew
Abstract : Background: Although Pisa syndrome and scoliosis are sometimes used interchangeably to describe a laterally flexed postural deviation in Parkinson's disease (PD), the imaging findings of Pisa syndrome in PD have not been previously studied in detail. Methods: Patients with Parkinson's disease and Pisa syndrome (lateral flexion >100 in the standing position) were examined clinically and underwent radiological assessment utilising standing radiograph and supine CT scan of the whole spine. Results: Fifteen patients were included in this observational study. The mean age was 72 years, mean duration of Parkinson's disease 15 years and mean duration of lateral flexion deformity 6 years. All patients had scoliosis on standing radiographs, and 12 had scoliosis persisting in the supine position. Scoliotic curves improved by a mean of 44% when patients moved from standing to supine. Only one quarter of patients with structural scoliosis had evidence of bony fusion on the side of their lateral deviation rendering their deformity fixed. Conclusions: Pisa syndrome describes a patient who lists to the side whereas scoliosis is defined by spinal curvature and rotation and may not be associated with lateral flexion. The finding of 'structural scoliosis' in Pisa syndrome should not preclude intervening to improve posture as most patients had little or no evidence of structural bony changes even when the deformity had been present for a number of years.